Correlation between the gut microbiota characteristics of hosts with severe acute pancreatitis and secondary intra-abdominal infection - Wang, Lihui; Zhang, Weijun; Dai, Simin; Gao, Yuan; Zhu, Cheng; Yu, Yuetian (Frontiers in Medicine, 2024)
Objective: To investigate the changes in the composition of intestinal microecology in severe acute pancreatitis (SAP) patients with or without intra-abdominal infection. Additionally, it aims to analyze the expression of antibiotic resistance genes to provide evidence for early warning of infectious diseases and the rational use of antibiotics. Methods: Twenty patients with SAP were enrolled in the study. According to whether the enrolled patients had secondary intra-abdominal infection, they were divided into two groups, each consisting of ten patients. Stool specimens were collected when they admitted to the emergency intensive care unit (EICU) and nucleic acid extraction was performed. Next-generation gene sequencing was used to compare the differences in intestinal microflora diversity and drug resistance gene expression between the two groups.The gut microbiota of patients in the infection group exhibited distribution on multiple clustered branches with some intra-group heterogeneity, and their flora diversity was compromised.The infected group showed an enrichment of various opportunistic bacteria in the gut microbiota, along with a high number of metabolic functions, stress functions to external signals, and genes associated with pathogenesis. Drug-resistant genes were expressed in the gut microbiota of both groups, but their abundance was significantly lower in the non-infected group.The intestinal microbiota of patients in the infection group exhibited distribution on multiple clustered branches with some intra-group heterogeneity, and their flora diversity was compromised. Additionally, drug-resistant genes were expressed in the gut microbiota of both groups, although their abundance was significantly lower in the non-infected group.